Infectious medical waste management during the COVID-19 pandemic in public hospitals of West Guji zone, southern Ethiopia - Hailu Lemma; Lechisa Asefa; Tesfaye Gemeda; Degefa Dhengesu (Elsevier, 2022)
Introduction: COVID-19 has swept through the world in a very short period; large volumes of medical waste are being generated in response to the pandemic. Hence, it is imperative to plan and develop evidence-based additional waste management systems. Objective: To assess infectious medical waste management system during the COVID-19 pandemic in public hospitals of the West Guji zone, southern Ethiopia, 2020. Methods: Institution-based cross-sectional study design was conducted from November 05-25/2020. To determine infectious medical waste generation rate, different color plastic buckets and bags was distributed to each ward of the hospitals. Then, its quantity was measured by using a calibrated weighing balance for seven consecutive days. An interviewer-administered questionnaire and an observational checklist were used to collect data related to the existing waste management system, and the knowledge, attitude and practice of waste handlers. The data were analyzed by SPSS version 25 and presented in tables, figures and texts as appropriate. Result: The average infectious medical waste generation rate was determined to be 2.1 kg/bed/day and/or 0.57kg/patient/day. Besides, there was limited segregation of infectious medical waste at the point of generation. Mixed medical waste was collected and transported by using open plastic bin and burned in a brick incinerator or/and dumped in an open field. Moreover, about 42%, 44.6% and 64.8% of the waste handlers had adequate knowledge; a positive attitude and adequate practice respectively. Conclusion: The average infectious medical waste generation rate is above the threshold value (0.2kg/bed/day) set by the WHO. Besides, its management was limited. There was also a gap in the knowledge and attitude of waste handlers towards infectious medical waste management during the COVID-19 pandemic.